Tourism Digital Marketing Tools and Views on Future Trends: Narrative Review - Kumar, Manoj; Chauhan, Dr. Sushil (The journal of contemporary issues in business and government, 2023)
The era of digital information has significantly changed international travel. Information and communication technology (ICT) is pervasive and intimately entwined with the consumer culture of the present. Offer: Inform, Plan, Order, Network, Establish Contacts, Stream, Execute, and Evaluate Transactions is what the acronym ICT stands for. These are granted benefits in the form of consumer information that is used to assess the marketability of goods and services as well as to forecast and influence consumer choices. IT has consequently had a significant impact on society, altering identity development, social conventions, and organisational structures. With its role as a testing ground, a global market, and an engine for the deployment of ICT, tourism is at the forefront of these advancements. This study compares current academic assessments to optimistic predictions and concluded that there are correlations between these advances and tourism and sustainability aims. The four stages of ICT adoption—Opportunity, Disruption, Immersion, and Seizure—seem to have shaped the development of tourism. These stages reflect new opportunities and threats as well as the demand for critical analyses of the effects of the ICT economy.